Analisis wacana kritis terhadap postingan media sosial tentang isu sosial di kalangan mahasiswa UIN Malang - Ameiliya, Faradina (Maliki Interdisciplinary Journal, 2026)
This study discusses how students of Maulana Malik Ibrahim State Islamic University Malang express and shape their views on social issues through social media posts. Social media has become an important space for students to share opinions, show attitudes, and respond to their surroundings. This research uses Norman Fairclough’s Critical Discourse Analysis to understand the meanings behind the texts and visuals posted by the students. The data were taken from public posts on Instagram and X (Twitter) related to issues such as environment, justice, education, and campus policies. The results show that students use clear language, specific word choices, and supportive visuals to strengthen the social messages they want to convey. This indicates that social media serves as an active space for students to build awareness and critical attitudes toward social issues.